Authenticity in Influencer Marketing, Building Trust and Addressing Distrust: A Case Study of Sadaf Beauty - Amini, Maryam (Université d'Ottawa / University of Ottawa, 2025)
Social media influencers are subject to an important - and constraining - paradox. On the one hand, they attract followers by presenting themselves as authentic while, on the other hand, they simultaneously use their popularity to promote products, as an act perceived by some followers as "inauthentic". Managing this contradiction and creating trust are crucial in their success and affects the number of people they reach. Successful influencer marketers negotiate this contradiction to inspire their followers' trust. However, while relying on these success factors, sometimes influencers lose control and cannot manage this contradiction which leads to followers feeling betrayed and losing trust. In this research, qualitative method based on case study of a successful Iranian Influencer, Sadaf Masaeli (Sadaf Beauty), assisted to observe how influencers lose control in managing different success factors and to analyze which factors make influencers to lose followers' trust. Sadaf was chosen as the second most influential beauty influencer of 2019 and the most influential luxury cosmetics influencer of 2019 in the world by Forbes (Claudel, 2019). She gained millions of followers from 2019 to 2022. However, in 2022 she lost thousands of followers. This research argues that incautious authenticity (indiscretion) and not setting concrete boundaries, especially in regard to sensitive topics, can cause distrust in followers.
Keywords: Influencer marketing; Trust; Distrust; Influencer; Instagram; Authenticity